Two widespread green Neottia species (Orchidaceae) show mycorrhizal preference for Sebacinales in various habitats and ontogenetic stages - Těšitelová, Tamara; Kotilínek, Milan; Jersáková, Jana; Joly, François-Xavier; Košnar, Jiří; Tatarenko, Irina; Selosse, Marc-André (Molecular ecology, 2015)
Plant dependence on fungal carbon (mycoheterotrophy) evolved repeatedly. In orchids, it is connected with a mycorrhizal shift from rhizoctonia to ectomycorrhizal fungi and a high natural (13)C and (15)N abundance. Some green relatives of mycoheterotrophic species show identical trends, but most of these remain unstudied, blurring our understanding of evolution to mycoheterotrophy. We analysed mycorrhizal associations and (13)C and (15)N biomass content in two green species, Neottia ovata and N. cordata (tribe Neottieae), from a genus comprising green and nongreen (mycoheterotrophic) species. Our study covered 41 European sites, including different meadow and forest habitats and orchid developmental stages. Fungal ITS barcoding and electron microscopy showed that both Neottia species associated mainly with nonectomycorrhizal Sebacinales Clade B, a group of rhizoctonia symbionts of green orchids, regardless of the habitat or growth stage. Few additional rhizoctonias from Ceratobasidiaceae and Tulasnellaceae, and ectomycorrhizal fungi were detected. Isotope abundances did not detect carbon gain from the ectomycorrhizal fungi, suggesting a usual nutrition of rhizoctonia-associated green orchids. Considering associations of related partially or fully mycoheterotrophic species such as Neottia camtschatea or N. nidus-avis with ectomycorrhizal Sebacinales Clade A, we propose that the genus Neottia displays a mycorrhizal preference for Sebacinales and that the association with nonectomycorrhizal Sebacinales Clade B is likely ancestral. Such a change in preference for mycorrhizal associates differing in ecology within the same fungal taxon is rare among orchids. Moreover, the existence of rhizoctonia-associated Neottia spp. challenges the shift to ectomycorrhizal fungi as an ancestral pre-adaptation to mycoheterotrophy in the whole Neottieae.
Keywords: Molecular Sequence Data; mixotrophy; Symbiosis; izotopy dusíku; ekosystém; germination; Sebacinales; taxonomické DNA čárové kódování; Europe; Evropa; Basidiomycota; Orchidaceae; Nitrogen Isotopes; Mycorrhizae; mykorhiza; izotopy uhlíku; symbióza; fylogeneze; Carbon Isotopes; Neottieae; molekulární sekvence - údaje; DNA Barcoding, Taxonomic; Ecosystem; Phylogeny; orchid mycorrhiza